Novel insights into the disease dynamics of B‐cell lymphomas in the Genomics Era. Issue 5 (6th March 2018) - Chan, Fong Chun; Lim, Emilia; Kridel, Robert; Steidl, Christian
Abstract: High‐throughput sequencing has significantly contributed to revealing the molecular underpinnings of B‐cell lymphomagenesis and disease progression. It is now a widely accepted concept that the diversity of clinical responses to front‐line therapy and the development of relapsed/refractory disease are in part explained by 'inter‐patient' genetic heterogeneity measurable by individual sets of somatic gene alterations in tumor genomes. Moreover, extensive 'intra‐tumor' heterogeneity on the genotypic and phenotypic levels is the product of ongoing tumor evolution and adaptation to various selective pressures during cancer initiation, progression, and therapeutic intervention. As the management of disease progression remains one of the most significant clinical challenges, it is becoming increasingly important to delineate how B‐cell lymphomas evolve over time and to develop progression‐related biomarker assays. Toward this goal, recent investigations have moved from studying lymphoma biology at initial diagnosis to doing so at multiple time points during the disease course. Profiling progressed tumors, and in particular paired biopsies at initial diagnosis and disease progression of the same patients, has led to novel insights into clonal tumor evolution and tumor microenvironment dynamics. This review discusses the latest findings on genomic alterations and microenvironment biology associated with relapsed/refractory B‐cell lymphomas, with a particular emphasis on alterations that are acquired or become more prevalent at disease progression. We also describe overarching tumor evolution patterns, and highlight emerging precision medicine methodologies that can aid in an improved understanding and management of relapsed/refractory disease. Copyright © 2018 Pathological Society of Great Britain and Ireland. Published by John Wiley & Sons, Ltd.